A reliable approach to customizing linux kernel using custom build tool-chain for ARM architecture and application to agriculture - Mahendra Swain; Rajesh Singh; Anita Gehlot; Md Farukh Hashmi; Shiv Kumar; Manish Parmar (International Journal of Electrical and Computer Engineering (IJECE), 2019)
ARM processors are receiving more attention as per IoT customized devices are concerned. A novel framework design tool for Linux kernel customization on ARM architecture has been illustrated. The tool is best suit from ARM based platformss like Raspberry pi, Beagle Bone, Intel Edison etc. The proposed techniques uses different tool chains for the kernel customization. The paper represents an integral framework that integrates all the cross compiling tools and simplifies the overall process. The framework has been used for the development of a customized kernel for Raspberry Pi on Ubuntu 14.04 host computer. The custom kernel has been ported in to Raspberry Pi and the performance evaluation has been done. Furthermore, the analysis aims to help users choose and configure their tracers based on their specific requirements to reduce their overhead and get the most of out of them. The testing of customized OS with raspberry Pi device in the field of agriculture. The smart node/mote is designed based on it to deploy in the agriculture field to test its feasibility. The group of nodes data is gathered using ThingSpeak cloud server. The gathered sensory data is analyzed and forecast on farmer’s mobile phone in the form of APP or handheld device for farmer.